2016
DOI: 10.1016/j.heliyon.2016.e00199
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the evaporation and condensation phenomena of lithium during the operation of a Li(d,xn) fusion relevant neutron source

Abstract: The flowing lithium target of a Li(d,xn) fusion relevant neutron source must evacuate the deuteron beam power and generate in a stable manner a flux of neutrons with a broad peak at 14 MeV capable to cause similar phenomena as would undergo the structural materials of plasma facing components of a DEMO like reactors. Whereas the physics of the beam-target interaction are understood and the stability of the lithium screen flowing at the nominal conditions of IFMIF (25 mm thick screen with +/–1 mm surface amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recent experiments related with the Facility for Rare Isotope Beams developed in the Argonne National Laboratory [121] have shown that flowing lithium can work in supersaturated conditions even with beam power densities four orders of magnitude above the 1 GW m −2 that the IFMIF Li target will experience. In addition, vaporization tests developed in the ELTL [96] have confirmed the validity of Herz-Knudsen-Langmuir analytical expressions to estimate the vaporization of Li during operation of the IFMIF (see section 3.2) [96,98].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recent experiments related with the Facility for Rare Isotope Beams developed in the Argonne National Laboratory [121] have shown that flowing lithium can work in supersaturated conditions even with beam power densities four orders of magnitude above the 1 GW m −2 that the IFMIF Li target will experience. In addition, vaporization tests developed in the ELTL [96] have confirmed the validity of Herz-Knudsen-Langmuir analytical expressions to estimate the vaporization of Li during operation of the IFMIF (see section 3.2) [96,98].…”
Section: Discussionmentioning
confidence: 61%
“…Vaporization rates are not a concern; a clear understanding of the behaviour has been obtained in specific tests carried out in ELTL [96] overcoming older confusing results [97]. Further, it has been demonstrated that the Hertz-Knudsen-Langmuir equation with η = 1.66 Schrage's accommodation factor is suitable for simple analytical calculations of the expected vaporization phenomena with an assessment for the IFMIF [98].…”
Section: Stability Of the LI Screen Absorbing The 2 × 5 Mw Beam Power...mentioning
confidence: 99%
“…The geometry of the vacuum chamber and lithium's low room-temperature vapor pressure prevent any lithium from reaching the ion gauge: the optimal path from the viewport to the gauge still requires five collisions with the walls of the vacuum chamber. The sticking coefficient of Li on stainless steel and Li is 1 to an excellent approximation [40][41][42][43][44], so we conservatively estimate that the probability for a lithium atom to reach the ion gauge is 10 −10 . Additionally, when lithium was initially deposited onto the viewport from the dispenser, a turbomolecular pump and a residual gas analyzer (RGA) were attached to the vacuum chamber near the ion gauge.…”
Section: Resultsmentioning
confidence: 99%
“…where m Li is the mass of an atom and k b is the Boltzmann constant [23]. Equilibrium vapor pressure p ν (T) data for solid and liquid elements was compiled by Honig and Kramer in [24].…”
Section: Appendix A: Lithium Evaporation From a Cpsmentioning
confidence: 99%
“…At first glance, Γ is just a complicated function of surface temperature T(t, z). However, the premise of a half-Maxwellian velocity distribution at the liquid-gas boundary implies the free expansion of unbound non-interacting particles [23]. This excludes the effect of collisions, the presence of impurities or the action of capillary forces in the effective rate of evaporation.…”
Section: Appendix A: Lithium Evaporation From a Cpsmentioning
confidence: 99%